SUSTAINABLE REFRACTORY BRICKS: ENHANCING CERAMIC KILN EFFICIENCY WITH RICE HUSK-BASED INSULATION - ERHUANGA, E. A.; FADAIRO, O.O. (Journal of Sustainable Energy)
This study explores the use of rice husk as a sustainable material for producing high thermal-insulating refractory bricks for ceramic kilns. Addressing challenges in agricultural waste management and energy efficiency, the research evaluates the technical feasibility, environmental benefits, and economic viability of integrating rice husk into refractory brick manufacturing. Experimental analyses assessed the silica content, thermal properties, porosity, compressive strength, and thermal expansion of rice husk-based bricks compared to conventional counterparts. Findings revealed a high silica content (45.40%) in rice husk, contributing to enhanced thermal insulation and energy efficiency in ceramic kiln operations. The rice husk-based bricks exhibited an estimated porosity of 27–43% and a compressive strength of up to 2 N/mm², demonstrating their suitability for kiln applications. Incorporating rice husk not only improved thermal performance but also promoted waste valorization by repurposing an abundant agricultural by-product, mitigating environmental hazards in rice-producing regions of Southwest Nigeria. Beyond the technical advantages, a preliminary cost analysis indicated the economic feasibility of adopting rice husk-based bricks in indigenous ceramic production. Further research is recommended to assess the life cycle environmental impact, including greenhouse gas emissions and energy consumption, using advanced assessment tools. Collaboration among local industries in strategic waste resource management could enhance raw material availability, lower production costs, and improve sustainability. This study presents a viable approach to reducing the ecological footprint of ceramic kilns by integrating agricultural waste into refractory brick production. By aligning with circular economy principles, the findings contribute to advancing sustainable and energy-efficient practices in the ceramics industry.